Regina Maria: armele literaturii în Marele război - Raluca Dună (Revista de Istorie și Teorie Literară)
The article discusses the diary Queen Mary began to write on the first day of World War One in Romania and kept on writing continuously during the war. But in the same period she wrote and published also other forms of war literature, with a strong propaganda effect, in Romania and abroad, namely My country, which appeared in London, New York and Toronto in 1916, also in a French edition, in Paris. In 1917 she published also a volume during the exile in Iasi where she is rewriting partly her diary and her style is strongly infused with personal issues and emotions. This volume contains a few texts published in the front journal România, so with a broad and special audience: soldiers in the trenches and in the hospitals. In the Diary she writes about these texts designed especially for the army and about the enthousiastic reactions of her audience. The article discusses the emotional, symbolic and war-propaganda effect of Queen Mary’s war literature published during 1916–1918, how it builds up an emotional and symbolical relationship between the royal author and the soldier-readers.